Superiority of fixed stem bipolar prosthesis over Austin Moore prosthetic in fracture neck femur - Naser, Mohd Abdul; Pathak, Ritesh; Ahmad, Ather (International Journal of Research in Orthopaedics, 2018)
Background: Hemi arthroplastyis a better option in treatment of fracture neck femur as it eliminates avascular necrosis of femoral head and non-union. It allows immediate weight bearing to return elderly patients to activity which helps in avoiding complications of recumbency and inactivity. The decision to perform hemi arthroplasty using a unipolar or bipolar prosthesis is a controversial issue. Both the prosthesis can be used even in remote areas both are cost effectives, good results can be achieved by general orthopaedic surgeons and post-operatively, it can be well adapted by Indian population. This study was done to compare the efficiency of Austin Moore’s prosthesis (AMP) and bipolar prosthesis for the management of intra capsular fracture neck femur in elderly patients. Methods: Patient’s above 60 years with fracture neck of femur were included. In all total 140 patients were randomly allocated for treatment by either AMP or bipolar prosthesis, in the department of Orthopaedics, IIMSR Medical College, Badnapur, Jalna between March 2014 to March 2017. The patients were followed up at 6 weeks, 12 weeks, 6 months and 1year. Functional outcome was assessed and compared with modified Harris hip score. Results: Modified Harris hip score was better with bipolar group as compared to AMP group. Functional activities like use of public transport were better with bipolar group. Complications like acetabular erosion were rare in bipolar group as comparison to AMP group. Conclusions: Fixed stem bipolar prosthesis is a superior option as compared to Austin Moore’s prosthesis.